Standar Audit Syariah Dan Peran DPS: Kesesuaian, Implementasi, dan Tantangan di Indonesia - Umiyati, Umiyati; Balqis, Siti Rania; Tsabitah, Hasna (Budgeting: Jurnal Akuntansi Syariah, 2025)
This study aims to comprehensively examine the relationship between sharia audit standards and the strategic role of the Sharia Supervisory Board (DPS) in ensuring sharia compliance in Sharia Financial Institutions (LKS) in Indonesia. Using a literature review approach, this study examines three main aspects: the suitability and implementation of sharia audit standards from both AAOIFI and PSAK IAI, the effectiveness of the DPS's role, and the challenges faced in supervisory practices. The findings reveal that although AAOIFI and PSAK IAI provide a comprehensive framework, their implementation in Indonesia remains suboptimal. LKS tend to adopt PSAK IAI as the primary reference since it aligns more closely with national regulations and accounting practices, while AAOIFI standards are often used as supplementary references to strengthen sharia compliance. Broadly, the key challenges faced by DPS lie in the limited availability of qualified human resources, the gap between sharia and accounting understanding, and the need to adapt to technological advancements and modern financial products. This study recommends strengthening the integration between internal and external audits with DPS, as well as enhancing the quality of sharia-based human resources and technological capacity.